2018
DOI: 10.1177/0954411918757812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gastric myoelectrical activity from the electrogastrogram signals based on wavelet transform and line length feature

Abstract: Electrogastrogram is used for the abdominal surface measurement of the gastric electrical activity of the human stomach. The electrogastrogram technique has significant value as a clinical tool because careful electrogastrogram signal recordings and analyses play a major role in determining the propagation and coordination of gastric myoelectric abnormalities. The aim of this article is to evaluate electrogastrogram features calculated by line length features based on the discrete wavelet transform method to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Several authors have worked with different wavelet analysis, for example, Barroso-Alvarado et al 18 used db4 wavelet analysis for the EGG signal, Nagendra et al 33 presented a summary of specific wavelet techniques, namely CWT, DWT, Stationary WT and Fractional WT. Many other studies applied ''db3'' for EGG signals to detect gastric arrhythmias, 9,11,22 Chaco´n et al 17 used fourth order Daubechies wavelet coefficients to evaluate signals from healthy and dyspepsia patients EGG, Sobral Cintra et al 32 showed that fitting a wavelet for EGG signals found with the standard ''db3'' to the fifth level wavelet provided the optimal parameterization values. In this study, ''db3'' was found to be the optimal wavelet for EGG signals at the fifth level and our results are partially consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have worked with different wavelet analysis, for example, Barroso-Alvarado et al 18 used db4 wavelet analysis for the EGG signal, Nagendra et al 33 presented a summary of specific wavelet techniques, namely CWT, DWT, Stationary WT and Fractional WT. Many other studies applied ''db3'' for EGG signals to detect gastric arrhythmias, 9,11,22 Chaco´n et al 17 used fourth order Daubechies wavelet coefficients to evaluate signals from healthy and dyspepsia patients EGG, Sobral Cintra et al 32 showed that fitting a wavelet for EGG signals found with the standard ''db3'' to the fifth level wavelet provided the optimal parameterization values. In this study, ''db3'' was found to be the optimal wavelet for EGG signals at the fifth level and our results are partially consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DWT analyzes the signal in different frequency bands with different resolutions by decomposing the signal into coarse approximation and detail coefficients. 11,23 The equation for CWT (equation ( 1)): b: translation of the function over x(t), ''c'': wavelet function, *: the complex conjugation operation, ''1''/O(|''a''|): a normalization factor confirming the energy for all values of a. But the main problem of CWT, it is highly redundant and provides oversampling of the main waveform, so more coefficients are generated.…”
Section: The Dwt Of Egg Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the EGG measurement is obtained from preterm babies longitudinally, the signal is expected to be highly non-stationary, and thus CWT is a more appropriate means used for time-frequency analysis. In the field of EGG [37][38][39][40][41][42][43][44] this is the first research report to utilize and implement CWT for determination of percentage time of non-stationary EGG rhythms spent in different gastric rhythm frequencies across three sub-feeding periods.…”
Section: Discussionmentioning
confidence: 99%